Decreased plasma APOA1 levels are associated with increased severity of placenta accreta spectrum disorders: a nested case-control study - Zeng, Shuai; Qu, Jiangxue; Jiang, Hai; Shi, Huifeng; Yan, Jie; Zhao, Yangyu; Chen, Lian (Frontiers in endocrinology (Lausanne), 2025)
Placenta accreta spectrum (PAS) disorders are a series of gestational diseases, with severe adverse outcomes. Apolipoprotein A1 (APOA1) is a lipid molecule that plays a role in cell invasion, inflammation and immune response. This study aimed to elucidate the relationship between APOA1 and PAS, as well as its adverse outcomes. This is a nested case-control study involving 118 patients with PAS and 118 non-PAS control women. Plasma APOA1 levels were evaluated at gestational weeks 24 to 35 by enzyme-linked immunosorbent assay. The clinical characteristics and pregnancy outcomes were recorded and analyzed in relation to APOA1 levels. The plasma APOA1 level in the PAS group was observed to be lower than that in the non-PAS group ( = 0.035). From 24 to 35 weeks of gestation, the trajectory of plasma APOA1 levels in the placenta percreta (PP) and placenta increta group exhibited a discernible decline. Maternal plasma APOA1 is a significant biomarker for the diagnosis of PAS and its adverse outcomes, particularly in the 32 to 35 weeks of gestation range for invasive PAS (AUC = 0.761, 95% CI 0.660-0.863, < 0.001), PP (AUC = 0.889, 95% CI 0.801-0.976, < 0.001), blood transfusion (AUC = 0.729, 95% CI 0.620-0.838, < 0.001) and hysterectomy (AUC = 0.884, 95% CI 0.790-0.978, < 0.001). A reduction in maternal plasma APOA1 levels was associated with the severity of PAS. APOA1 may serve as a biomarker for invasive PAS, blood transfusion and hysterectomy in late gestation.